Studi Perbandingan Performa Pertumbuhan Larva Ikan Kakap Putih (Lates calcarifer) Strain Lokal dan Strain Australia di BBRBLPP, Gondol, Buleleng, Bali - Rama Nia Julia Putri; Syarifatul Jamil; Resty Oktavianingtyas Pratiwi; Suciyono; Hendra Agung Kurniawan (Jurnal Akuakultur Rawa Indonesia, 2026)
Seabass (Lates calcarifer) is a fish with high prospects for development in Indonesian aquaculture. Selecting superior seeds is one effort to increase aquaculture production. Currently, BBRBLPP is actively producing larvae cultivation of local and Australian strains of Seabass. This study aims to evaluate the superiority between both strains. The method used in this study is descriptive. Parameters observed in this study include egg quantity and quality, as well as larval growth rate. The results showed that the local strain produces fewer eggs than the Australian strain, with a higher survival rate. Based on the comparative analysis conducted, it can be concluded that the local strain of Seabass (Lates calcarifer) has the advantage of superior seed quality, while the Australian strain has a higher egg quantity.